New media in journalism education (Herald of Journalism, 2022)
This article is about digital century, which change journalism education, information sphere , mass media, between press and electronic mass communications. The new model multimedia, convergence journalism cultivated in Universities systems of education, which prepare multimedia journalists for the modern media market. The creation different media information contexts are need from students new knowledge, specific methods, skills, which there are give on the Faculty of journalism of the Kazakh National University named after Al-Farabi.The main goal – to show how modern journalism, mass communication are changes in era of global- ization and digitalization, how changes the demands in educational process under influence new media, how new subjects appear in process of education.Key words: Modern journalism, multimedia, convergence, digital era, Information Kazakhstan.